2006
DOI: 10.2304/plat.2005.5.2.153
|View full text |Cite
|
Sign up to set email alerts
|

Is the Teaching of Statistical Calculations Helpful to Students' Statistical Thinking?

Abstract: The teaching of statistics to psychology undergraduates has traditionally included formulae and methods for conducting statistical tests without the aid of a computer. Does this requirement to master the formulae encourage deeper understanding or merely provoke anxiety? The relationship between competence in calculation and statistical thinking was examined using questions from an exam set at the end of a compulsory first year module. In addition, scores on a premodule test and coursework grades were recorded,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Psychology students were chosen for this study as, while the course is not mathematics-based, it nevertheless consists of a heavy quantitative component involving statistics. Despite the importance of statistics in the psychology curriculum, it nevertheless remains one of the least liked and poorly performed components of the course (Dempster & McCorry, 2009;Seabrook, 2005) with students tending to do very badly on statistics exams (British Psychological Society, 2003).…”
Section: Participantsmentioning
confidence: 99%
“…Psychology students were chosen for this study as, while the course is not mathematics-based, it nevertheless consists of a heavy quantitative component involving statistics. Despite the importance of statistics in the psychology curriculum, it nevertheless remains one of the least liked and poorly performed components of the course (Dempster & McCorry, 2009;Seabrook, 2005) with students tending to do very badly on statistics exams (British Psychological Society, 2003).…”
Section: Participantsmentioning
confidence: 99%
“…A further aim was to promote motivation and engagement with the statistical content. Statistical thinking and metacognitive skills are difficult to measure (Seabrook, 2006) and without an experimental approach, it is difficult to link changes to specific aspects of the assessment strategy. Much more straightforward is asking students about their use of feedback and to do this we distributed a short questionnaire to students just completing the course and to recent students for whom we had contact details.…”
Section: Evaluation and Development Of Assessment Strategymentioning
confidence: 99%
“…Additionally, instructors may worry that simultaneously teaching programming and challenging statistical concepts may be too burdensome for introductory statistics students (i.e., the high cognitive load would prohibit effective learning; Sweller, 1994). While teaching statistics via hand calculations can contribute to students' computational understanding, the effect is quite small (Seabrook, 2006). Additionally, recent work demonstrated that priming mathematical calculation prompts students to recall and rigidly apply formulae, rather than try to make sense of a problem (Lawson et al, 2021).…”
mentioning
confidence: 99%